Research and prospect of standard for biometric multi-modal fusion used with mobile devices - Guanchen LIN; Zhifei WANG (Dianxin kexue)
Aiming at the problem of inconsistent biometric multi-modal fusion technology framework for mobile devices and lack of standards, a unified technical framework of multi-modal fusion standards was proposed.Firstly, the current status of standardization related to biometric used with mobile device was analyzed.Secondly, the local recognition and remote recognition application modes of mobile device biometrics standards were studied, and then four sub-multimodal fusion classification methods of multi-feature, multi-algorithm, multi-instance, and multi-sensor were analyzed and proposed.Then, four levels of multi-modal fusion were researched and proposed: sample-level fusion, feature-level fusion, score-level fusion, and decision-level fusion, and a standard technical framework for biometric multi-modal fusion for mobile devices was proposed.Finally, prospects for the application of biometric multi-modal fusion technology were given.